Editrorial - Bozalek, Vivienne (Critical Studies in Teaching and Learning, 2023)
We are delighted to be bringing out this first edition of Critical Studies in Teaching and Learning. The planning for the journal began some four years back at the University of the Western Cape (UWC) in Cape Town, as part of the renewal of emphasis on the scholarship of teaching and learning at the institution. An editorial committee was formed by academics mainly from UWC and the other three higher education institutions in Cape Town, - Brenda Leibowitz and Cecilia Jacobs (Stellenbosch University), Chris Winberg and James Garraway (Cape Peninsula University of Technology), Dick Ng’ambi, Moragh Paxton and Cheryl Hodgkinson - Williams (University of Cape Town), Sherran Clarence and Vivienne Bozalek (University of the Western Cape), as well as Melanie Walker (University of the Free State), Denise Wood (University of South Australia) and Masebala Tjabane (Higher Education Learning and Teaching Association of Southern Africa (HELTASA) to which the journal is affiliated). This committee deliberated for some time on the exact focus and form of the journal.